Rural–urban differences in quality of life and associated factors among community-dwelling older persons in Oyo state, South-Western Nigeria. (2021)
Aim The decline of health and functional status as a result of old age makes it necessary to assess the Quality of Life (QoL) among older persons. There is, however, limited information in this regard from low and middle-income countries such as Nigeria. This study compares the QoL and associated factors among rural and urban community-dwelling older persons (≥ 60 years) in Oyo State, Nigeria. Subject and methods A cross-sectional, comparative community-based study was carried out using an interviewer administered, semi-structured questionnaire. The QoL was determined using the World Health Organisation Quality of Life Brief Scale (WHOQOLBREF). Data were analysed using Stata version 14 at p < 0.05. Results Overall, 1,180 (588 urban and 592 rural-dwelling) respondents were interviewed. Females constituted more than half of the respondents in both communities, accounting for over two thirds (69.2%) of the population. The mean QoL scores were similar in the psychological (54.2 ± 7.4) and environmental (54.7 ± 9.5) domains. However, the mean score for the physical domain was 69.2 ± 17.0 and 74.1 ± 12 for the social domain. There was no statistically significant difference between mean scores of the QoL in the two locations except in the environmental domain (p < 0.05). Good self-rated health was a common positive predictor of higher mean scores across the four domains in both the rural and urban settings (p < 0.05). Conclusion The rural–urban differences in the mean quality of life scores in the environmental domain in the study and poorer scores in the psychological and environmental domains necessitate areas for targeted intervention and more in-depth research